Tecnologia alternativa para o monitoramento de poluentes gasosos - Saavedra Mendoza, Andy Avimael (2016)
In Brazil and in particular in the State of Paraná West Region there are several activities that emit gaseous pollutants. Specifically, the proximity of urban areas, pig farming, cattle raising, poultry, the wastewater treatment plants and processing industries of refrigerators waste and slaughter of pigs, cattle, poultry and fish have bothered the population the bad smell prevalent these activities. The qualification and quantification of gaseous emissions are of extreme importance for the environmental assessment and also to the use/treatment/control the emission of gaseous pollutants, because the choice of prevention methods and also the corrective methods depend on this information. In this context, the general objective of this study was to development an alternative technology for transient monitoring, remote, individual or simultaneous gaseous pollutants including H2S, SO2, CO and CO2. For this purpose the methodology included the realization of 4 steps: 1) Physical and chemical characterization (qualitative and quantitative) of gaseous pollutants and their sources of generation (properties of pig farming and refrigerators waste processing industries); 2) proposition/development/ design/manufacturing/assembly of alternative technology; 3) operational tests in laboratory scale and in real operating condition; and 5) evaluation of the requirements of novelty and intellectual property protection in the form of patent. The result of the work was an alternative technology for transient monitoring of gaseous equipped with the following attributes: performs continuous monitoring (every minute) concentrations of H2S, SO2, CO and CO2; The monitoring results are presented in tables and graphs and dynamic can be viewed remotely at a distance of 500 m by means of a communication radio frequency (RF) system; by means of a computer program with a visual interface technology enables storing and exporting the monitored data to an Excel spreadsheet; and lastly, the existence of the Internet connection, the technology also allows the sending of data monitored continuously, to a virtual server and thus enables remote monitoring with unlimited distance between the point of monitoring and viewing point / data processing. According to the results presented above and based on the technical and constructive character features, the alternative technology developed was patenting object at the National Institute of Industrial Property-INPI.